The Influence Of Motivation And Training On The Productivity Of Sales Representatives At Pt Arista Mitra Lestari, West Java, With Competence As A Mediating Variable - Didin Hendriana; Dudung Hadiwijaya; M.Imam Mutaqijm (UNIVED Press, 2024)
This research aims to analyze the influence of motivation and training on productivity, with competence as a mediating variable. The research type employed is explanatory research, using the survey explanatory method with a quantitative approach. The sample consists of 99 respondents, namely sales representatives at PT. Arista Mitra Lestari, Region 3 Cirebon, West Java. The sample was selected using purposive sampling. Data analysis method employed Structural Equation Modeling-Partial Least Square (SEM-PLS), and the software used is SmartPLS 3.00. The research results indicate that motivation significantly influences competence. Training significantly influences competence. Motivation significantly influences productivity. Training significantly influences productivity. Competence significantly influences productivity. Motivation significantly influences productivity mediated by competence. Training significantly influences productivity mediated by competence. The conclusion of this research has implications for PT. Arista Mitra Lestari, Region 3 Cirebon, West Java, in improving the performance of its sales representatives. PT. Arista Mitra Lestari is encouraged to enhance motivation and training to boost the productivity of sales representatives, with competence playing a crucial role in increasing the sales of products in PT. Arista Mitra Lestari, Region 3 Cirebon, West Java